A Continuously Tunable Silicon Double-Microring Filter With Precise Temperature Tracking - Yang Ren; David Perron; Fnu Aurangozeb; Zhiping Jiang; Masum Hossain; Vien Van (IEEE Photonics Journal, 2018)
We demonstrate continuous tuning of a second-order silicon microring filter over the full 7.8-nm FSR of the resonators using the thermo-optic effect. Strongly correlated linear relationships between the heater powers and the filter center wavelength were obtained even in the presence of thermal crosstalks in the resonant frequencies and coupling coefficients, which allowed the filter to be tuned to any arbitrary wavelength with an accuracy of ±27 pm without the need for further optimization. We also demonstrate the use of integrated on-chip thermistors for precise tracking of the local temperatures of the microring resonators, thereby providing an indirect mechanism for monitoring the center wavelength and spectral characteristics of the filter.